Analisis Tren Digitalisasi dalam Pembelajaran Bahasa Arab: Studi pada Akun TikTok Kursus Arab Al-Azhar - Sartika Alpianti Manurung; Raudhatul Jannah; Mutia Syahdina; Sahkholid Nasution (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2025)
This study aims to analyze the trends of digitalization in Arabic language learning, focusing on the TikTok account of the Al-Azhar Arabic Course. In the modern era, the rapid development of digital technology has transformed educational practices, making learning processes more interactive, flexible, and accessible. TikTok, as one of the most popular social media platforms, offers a new approach to delivering educational content through engaging short videos. This research employs a descriptive qualitative method to understand the use of TikTok as a learning medium, including content patterns, user responses, and its effectiveness. Data were collected through content observation, interviews with account managers and users, and documentation of interactions on the platform. The findings indicate that the Al-Azhar Arabic Course TikTok account successfully captures the interest of young audiences with its varied and interactive content. Active interaction between account managers and users also enhances student engagement in the learning process. Despite challenges related to content quality and technological disparities, this study demonstrates that TikTok holds significant potential as an educational tool for introducing Arabic language to a broader audience. The research recommends that account managers continually update their content and evaluate its relevance and quality.